Water (R718) turbo compressor and ejector refrigeration/heat pump technology - Šarevski, Milan N.; Sarevski, Vasko N. (Butterworth-Heinemann, 2016)
Water (R718) Turbo Compressor and Ejector Refrigeration/Heat Pump Technology provides the latest information on efficiency improvements, a main topic in recent investigations of thermal energy machines, plants, and systems that include turbo compressors, ejectors, and refrigeration/heat pump systems. This, when coupled with environmental concerns, has led to the application of eco-friendly refrigerants and to a renewed interest in natural refrigerants. Within this context, readers will find valuable information that explores refrigeration and heat pump systems using natural refrigerants, polygeneration systems, the energy efficiency of thermal systems, the utilization of low temperature waste heat, and cleaner production. The book also examines the technical, economic, and environmental reasons of R718 refrigeration/heat pump systems and how they are competitive with traditional systems, serving as a valuable reference for engineers who work in the design and construction of thermal plants and systems, and those who wish to specialize in the use of R718 as a refrigerant in these systems.